AKIBAT HUKUM TERHADAP PERKAWINAN ADAT BATAK SIMALUNGUN MARHAJABUAN TIDAK TERLAKSANA ADAT NAGOK DI DESA NAGORI DOLOK KABUPATEN SIMALUNGUN - Yohana Dwi Putri Damanik; Hamdani Ma’akir; Dimas Dwi Arso (UNIB Press, 2025)
The traditional marriage of Batak Simalungun Marhajabuan does not carry out the Nagok custom in Nagori Dolok Village, Simalungun Regency is a marriage ceremony that does not carry out full customs, the marriage only carries out a part of the series of traditional ceremonies so that it cannot complete all applicable customary procedures. This research method is a empirical legal research with a qualitative approach. The results of the study show that the factors that cause Marhajabuan not to carry out the Nagok custom according to the Batak Simalungun customary law in Nagori Dolok Village, Simalungun Regency are divided into two, namely internal factors consisting of six, namely parents who are less able to afford the cost of the party or regarding the cost of partadingan (honest money), the parents of the woman did not approve of the marriage of the married couple, the bride and groom had committed a violation of customs, the man and the woman were of the same clan, the man and woman were matched by both parents and the lack of understanding of the bride and groom or parents of the custom. Meanwhile, there are two external factors, namely social change and modernization and inter-tribal marriage and efforts to inaugurate Marhajabuan only through mangadati. Meanwhile, as a result of the law against Marhajabuan, the Nagok custom is not carried out according to Batak Simalungun customary law, namely the marriage that has been carried out is not recognized customarily, subject to customary sanctions or fines, the children of the couple cannot carry out the marriage using the custom, and if one of these married couples dies, the first procession that must be carried out is the ceremony Stuart.